Early Student Support to Investigate the Role of Sea Ice-Albedo Feedback in Sea Ice Predictions - Bitz, Cecilia M (2014)
The overarching goals of this project are to understand the role of sea ice-albedo feedback on sea ice predictability, to improve how sea-ice albedo is modeled and how sea ice predictions are initialized, and then to evaluate how these improvements influence inherent sea ice predictability.